MANAJEMEN KLUB VAMOS MATARAM DITINGKAT LIGA PROFESIONAL - julinur hafid; Amung Ma'mun; Dikdik Zafar Sidik (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
This paper is motivated by the achievements of the Vamos Mataram futsal club in the Indonesian professional futsal league because it won the season 3 season in a row, namely the 2017, 2018 and 2019 seasons. The purpose of this study is to assist Vamos management in helping their team at the professional futsal league level. This article provides planning for change management with long-term planning, which discusses teams and information systems, which will provide relevant information for decision makers in planning the right time. The method used in this study is a literature review and interviews with informants involved in the players, coaches, and official team of Vamos. The results of this study see that Vamos management is a successful management, it is seen from the achievements of a successful team. Therefore, the authors agree that management success and a long-term coaching strategy will support the achievements of the club, the national team, and can become a culture in the wider community.